Spatio-temporal distribution of foot and mouth disease outbreaks in Western Amhara region from January 2018 to June 2023 - Endeshaw Demil; Belege Tadesse (PLoS ONE, 2025)
Foot and mouth disease (FMD) is a contagious and economically important viral disease of cloven hoofed animals caused by FMD virus. This retrospective study was conducted to determine the spatio-temporal distribution, estimate the morbidity and case fatality of FMD outbreaks in Western Amhara region of Ethiopia from January 2018 to June 2023. The FMD outbreaks reported to Bahir Dar regional laboratory and confirmed by Sandwich ELISA were used for this study. A total of 164 FMD outbreaks were reported in Western Amhara region of Ethiopia between 2018 and 2023. The highest and lowest number of FMD outbreaks were reported in 2022 (n = 42 outbreaks) and 2018 (n = 9), respectively; however, there was no statistically significant difference in the occurrence of FMD outbreaks between years (p = 0.224). There was no significant difference in case fatality and morbidity rates between years (p> 0.05). Based on months, high number of outbreaks were reported during January (n = 32) across all years and the lowest during April, June and September (n = 3 for each district). There was statistically significant difference in the occurrence of FMD outbreaks between months (p < 0.001). On average, 13.66 FMD outbreaks were reported in each month. All administrative zones in Western Amhara region reported more than one FMD outbreaks during January 2018 –June 2023. The highest and lowest outbreaks were reported from East Gojjam Zone (62 outbreaks/6 district years), and Bahirdar Special Zone and Gondar Town (2 outbreaks for each district). There was no statistically significant difference in the occurrence of FMD outbreaks between the administrative zones (p > 0.05). District wise, the highest and lowest number of FMD outbreaks were reported from Goncha Siso district (n = 14) and Banja, Simada, Zigem, Machakel, Debre Elias and Debark (with one outbreak in each district). This study indicated that FMD outbreaks regular occurs in Western Amhara region. To reduce the occurrence and spreading, animal movement and transport should be controlled, and vaccination should be implemented regularly.